Literature Study: Teaching Modules Based on Realistic Mathematics Approach to Improve Learning Outcomes of Elementary School Students Between 2019 - 2024 - Iftinawati, Sri; Handoyo, Eko; Wardani, Sri; Subali, Bambang; Widiarti, Nuni (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This literature review departs from the problems in learning mathematics in elementary schools related to teaching abstract material, such as fractions, which affects the low achievement of student learning outcomes. This literature review aims to theoretically analyze the impact of using teaching modules based on the Realistic Mathematics Approach (PMR) in improving student learning outcomes in primary schools. The method used in this review is a Systematic Literature Review (SLR) covering 25 articles from five databases: Google Scholar, DOAJ, Sinta, ResearchGate, and Scopus. The articles were keyworded "teaching module", "realistic mathematics", "learning outcomes", "primary school", "RME", and "teaching module", using the Boolean operator "AND". The results showed that using PMR-based teaching modules positively impacted student learning outcomes. The main findings of this literature review are: 1) Better understanding of math concepts; 2) Increased active participation of students; 3) Increased critical thinking and problem-solving skills; 4) Teaching modules are considered practical and feasible; 5) Positive responses from teachers and students. In conclusion, PMR-based teaching modules have proven effective in improving the learning outcomes of elementary school students. This study recommends the need for development and training for teachers in designing PMR-based teaching modules to produce more relevant and efficient learning experiences in elementary schools.